2014
DOI: 10.1016/j.rbmo.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells and related cytokines in unexplained recurrent spontaneous miscarriage at the implantation window

Abstract: Unexplained recurrent spontaneous abortion (RSA) might be caused by the mother's immunological rejection of the fetus. In this cross-sectional study, the percentage of T helper 17 (Th17), T regulatory (Treg) cells and their cytokines as the main players of immunomodulation in peripheral blood lymphocytes during the luteal phase of 20 women with unexplained RSA were compared with 20 normal non-pregnant women. The percentage of Treg cells in the former was significantly lower compared with controls. The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 33 publications
2
60
0
4
Order By: Relevance
“…Complementary DNA was then synthesized using TaqMan Gold RT-PCR Kit (Takara, Otsu, Shiga, Japan), according to the manufacturer's instructions. A quantitative real-time PCR was performed for HTLV-1 HBZ and Tax mRNA, and a cellular reference gene, B2M [33], using TaqMan method reagent target kits (Applied Biosystems, Foster City, CA, USA) in accordance with the manufacturer's instructions. Primers and probes for Tax, HBZ, and B2M mRNA expression are summarized in Table 1.…”
Section: Hbz and Tax Mrna Expressionmentioning
confidence: 99%
“…Complementary DNA was then synthesized using TaqMan Gold RT-PCR Kit (Takara, Otsu, Shiga, Japan), according to the manufacturer's instructions. A quantitative real-time PCR was performed for HTLV-1 HBZ and Tax mRNA, and a cellular reference gene, B2M [33], using TaqMan method reagent target kits (Applied Biosystems, Foster City, CA, USA) in accordance with the manufacturer's instructions. Primers and probes for Tax, HBZ, and B2M mRNA expression are summarized in Table 1.…”
Section: Hbz and Tax Mrna Expressionmentioning
confidence: 99%
“…Th17 are derived in response to TGFβ and IL-6 as well as inflammation [41]. They secrete IL-17, -21, -22 [41,[81][82][83][84][85][86] cells inhibit one another and are both regulated by Treg cells. An overexpression of Th1 immunity has been thought to play a role in RPL.…”
Section: T-helper Lymphocyte-2 Cellsmentioning
confidence: 99%
“…Increased levels of Th17 cells have been found in the decidua and peripheral blood of patients with RPL compared to their controls. They have a negative impact on the early stages of pregnancy [42,76,[82][83][84][85]89].…”
Section: T-helper Lymphocyte-17 Cellsmentioning
confidence: 99%
“…Animal studies have found evidence of a link between successful pregnancy and the predominant levels of anti-inflammatory cytokines relative to inflammatory cytokines. In human studies, patients with recurrent abortion have been found to have high levels of inflammatory cytokines and low levels of anti-inflammatory cytokines (Demirturk et al, 2014;Saifi et al, 2014;Bahadori et al, 2014;Potdar et al, 2005). factor alpha (TNF-ɑ) (Qu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%